The Market Microstructure Approach to Foreign Exchange: Looking Back and Looking Forward - Michael R. King; Carol Osler; Dagfinn Rime (Norges Bank, 2013)
Research on foreign exchange market microstructure stresses the importance of order flow, heterogeneity among agents, and private information as crucial determinants of short-run exchange rate dynamics. Microstructure researchers have produced empirically-driven models that fit the data surprisingly well. But FX markets are evolving rapidly in response to new electronic trading technologies. Transparency has risen, trading costs have tumbled, and transaction speed has accelerated as new players have entered the market and existing players have modified their behavior. These changes will have profound effects on exchange rate dynamics. Looking forward, we highlight fundamental yet unanswered questions on the nature of private information, the impact on market liquidity, and the changing process of price discovery. We also outline potential microstructure explanations for long-standing exchange rate puzzles.
hdl:11250/2496697
Keywords: F31; G12; G15; C42; C82; 330; exchange rates; market microstructure; order flow; information; liquidity; electronic trading